Matters arising: cost-utility and cost-effectiveness analysis of disease-modifying drugs of relapsing–remitting multiple sclerosis: a systematic review - Carlo Lazzaro; Roberto Bergamaschi; Mauro Zaffaroni; Rocco Totaro; Damiano Paolicelli (Health Economics Review)
Abstract Background In their interesting systematic review, Gallehzan et al. quoted our article Cost-utility analysis of teriflunomide in naïve vs. previously treated patients with relapsing–remitting multiple sclerosis (RRMS) in Italy. While we are grateful to Gallehzan et al. for their interest in the aim of our research, we would like to clarify some points. Methods We compare Gallehzan et al.’s statements about our article with the original publication. Results Gallehzan et al. omitted or misreported some relevant methodological issues and findings presented in our article. As far as methods are concerned, the main omissions were the 7-year time horizon of our study (that falls in between the 5–10 years range mentioned by Gallehzan et al. for other contributions) and the number of simulated RRMS naïve patients (1000). Regarding findings, Gallehzan et al. mistook the 0.480 incremental Quality-Adjusted Life Year gained by RRMS naïve patients vs. RRMS experienced patients on teriflunomide for the base case Incremental Cost-Utility Ratio (ICUR) calculated according to the societal viewpoint. In fact, for both the healthcare sector and societal perspectives adopted in our Markov model-based cost-utility analysis, the baseline results showed teriflunomide in RRMS naïve patients to be strongly dominant (that is, producing more QALYs and being, at the same time, cost-saving) vs. RRMS experienced patients. Therefore, the calculation of the two ICURs was not necessary. Conclusions As systematic reviews play a remarkable role in disseminating health economic research, a careful description of the methods and the findings reported in the included studies is of paramount importance.